Evaluasi pembiayaan kesehatan pada program tuberkulosis: A systematic review - Dewi Wulan Anugrah Sari; Sartini Risky; Irlan Septian Hidayat; La Ode Liaumin Azim (Holistik Jurnal Kesehatan, 2026)
Background: Background: Tuberculosis (TB) remains a major public health problem worldwide, particularly in developing countries, including Indonesia. This disease impacts not only individual health but also social and economic aspects of society. The high incidence of TB leads to an increased need for health services, long-term treatment, and the strengthening of sustainable disease control systems. Health financing is a critical component of the success of tuberculosis (TB) control programs, particularly in ensuring access to services and the sustainability of treatment. Purpose: To evaluate health financing in tuberculosis programs. Method: This study is a Systematic Literature Review (SLR) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. A systematic literature search was conducted in several international scientific databases, namely PubMed, Scopus, ScienceDirect, Web of Science, and Google Scholar. The search process was conducted from January to March 2026 using a combination of keywords and Boolean operators (AND, OR) to identify relevant articles. Results: The review findings indicate that health financing contributes to increased TB service coverage, treatment success, and strengthened disease surveillance programs. However, the implementation of TB program financing still faces various challenges, such as budget constraints, dependence on external donors, unequal access to services, and a high financial burden borne by patients. Conclusion: A sustainable, integrated, and needs-based health financing system is needed to effectively support tuberculosis eradication.   Keywords: Evaluation; Financing; Health Programs; Tuberculosis.